النظام القانوني للالتحاق بالوظائف العمومية في التشريع الجزائري (مجلة الواحات للبحوث والدراسات, 2023)
ملخص:        يعتبر قطاع الوظيفة العمومية في الجزائر من أهم القطاعات الحيوية، باعتباره الآلية القانونية التي تستطيع من خلالها الدولة تنفيذ السياسة العامة لها، حيث يعد هذا القطاع من بين أهم القطاعات التي تتوقف عليها نشاطات الدولة في مختلف الميادين، خاصة ما تعلق منها بإدارة المرافق العامة التي تعد من بين أبرز مظاهر الدولة في ممارسة نشاطها وسياستها العامة، والآلية التي تسمح لها بإدارة شؤون المواطنين وإشباع حاجاتهم المختلفة. لأجل ذلك أخضع المشرع الجزائري عملية الالتحاق بالوظائف العمومية للعديد من الضوابط القانونية التي تشمل في مجموعها المبادئ، الشروط، والإجراءات المنظمة لعملية التوظيف، وأنماطه.كلمات دالة:الوظيفة العمومية، التوظيف، المؤسسات والإدارات العمومية.   Abstract:          Algeria's public employment sector is one of the most vital. as the legal mechanism through which the State can implement its public policy, This sector is one of the most important sectors on which the State's activities in various fields depend. in particular those relating to the management of public facilities, which are among the most prominent manifestations of the State's activity and public policy, The mechanism that allows it to manage citizens' affairs and satisfy their different needs. To this end, Algeria's legislator has subjected the process of admission to public office to numerous legal controls, which include, in their entirety, principles, conditions, procedures governing the recruitment process and its patterns. Key words:public service, employment, Public Institutions and Departments.